Glacier snowline altitude variations in the Pamirs, Tajikistan, 1998-2013: insights from remote sensing images. Issue 12 (2nd December 2017) - Zhang, Qibing; Kang, Shichang
ABSTRACT: Snowline altitude (SLA) variations can reflect glacier changes. The glacier SLAs in the Pamirs of Tajikistan were investigated using Landsat, ASTER and ALOS images acquired at the end of the ablation season and the method of visual interpretation. The average SLA in the western Pamirs was 4355 ± 134 m above sea level (a.s.l) from 1998 to 2013, while it was 5050 ± 35 m a.s.l in the eastern Pamirs, SLAs in the eastern Pamirs were higher than those in the western Pamirs. From 1998 to 2013, the SLA rose by 0.3 m per year (m year −1 ) in the western Pamirs but descended by 5.1 m year −1 in the eastern Pamirs. Glaciers in the Pamirs were stable or advancing, which is consistent with the Pamir-Karakoram anomaly.